Pembelajaran Menyanyikan Lagu Daerah Menggunakan Metode Drill pada Siswa Kelas VII SMP Negeri Muara Kulam - Saipi, Muhammad; Firmansyah, Feri; Firmansyah, Dedy (Indonesian Research Journal on Education, 2023)
Singing folk songs in unison or individually folk songs is still low, especially for subjects that lead to performance practices, this is seen from the minimum completeness criteria because there is still a lack of knowledge about tonic intonation and articulation. This research is to find out whether learning to sing folk songs using the drill method can improve the learning outcomes of class VII students of SMPN Muara Kulam. The method used in this study is a qualitative description of the data sources used areclass VII students and Mrs. Dian Permata Sari, S. Pd as a teacher of SMP Negeri Muara Kulam, themethod used in this learning is the drill method of data collection techniques in this study, namelyobservation, interviews and documentation based on the data analyzed which was carried out in theconclusion that learning to sing folk songs using the method drill on class VII students of SMP Negeri Muara Kulam can improve student learning outcomes can be seen from the value before using the drill method and after using the drill method before using the drill method subject the number of students in class VII is 29 "very good" 3 students, with the criteria " good' numbered 26 people. After using the subject drill method as many as 29 students of class VII with the criteria of "very good" totaling 22 students, with the criteria of "good" 7 students. In the implementation of the cultural arts teacher hasapplied the right method this can be seen from the learning outcomes of students who get an average score average 86 -100.